Enhancing power quality in solar-wind grid-connected systems through soft computing techniques - Kathirvel, Jayashree; Sreenivasan, Pushpa; Mohammed, Soni; Sethi, Rabinarayan; Syamala, Maganti (Institute of Advanced Engineering and Science, 2024)
This work intends to improve estimates of solar and wind energy generation through the application of resilient backpropagation control and substantial power evolution strategy (SPES) algorithms. In comparison to particle swarm optimization and genetic algorithms, the main goal is to minimize predicting mistakes. These methods increase grid reliability by lowering total harmonic distortion (THD) and improving power quality when integrated with the IEEE-9 bus standard. In order to evaluate the hybrid system's transient and steady-state reactions, the study also highlights the importance of bolstering operation and control. A revolutionary deep learning-based approach is also suggested for predicting wind and solar hybrid energy. The power grid's efficiency and dependability in handling renewable energy sources have significantly improved, according to the results.